Development of model reading skill builders for Filipino students in high school - Ledesma, Lydia
The value of reading in modern life cannot be gainsaid. An awareness of this as impelled educators to study the problems in teaching reading and to suggest measure for solving them. Research has pointed out two major problems confronting reading programs in the Philippines. They are: 1). Inadequacy of reading materials which ae geared to the experiental background, culture, and interest of Filipino students, and which provide training for multiple skills. 2.) Insufficiency of materials to provide for the needs of schools throughout the country. Studies abroad, though expensive and varied in scope, are still inadequate and insufficient for the needs of Filipino students. Since the subject matter of these studies is not within the experiential background and culture of Filipinos, they are not likely to generate the desirable feeling, attitudes, and habits which are the ultimate goals of all reading programs. They would not give students that feeling of security and confidence which is essential for exerting effort toward further progress and achievement. Insufficient reading materials cannot provide the training necessary for developing reading skills. Related studies in the Philippines, though constructed mostly with subject matter within the context of the Filipino student's environment and culture, are inadequate for training because the materials are based mainly on paragraphs developing one skill. a complete program should have materials with whole selections as basis for the exercises which train for multiple skills. The present study, Development of Model Reading Skill Builders for Filipino Students in High School is an attempt to help solve the two problems of our reading programs by formulating forty reading comprehension materials on two levels of difficulty and by gearing these materials to the background, interests, and needs of the Filipino student in high school. Chapter 1 discusses in detail the role of reading in modern life and the steps taken by educators to improve reading programs in school as a result of their recognition of this role. It also describes and evaluates related studies abroad and inthe Philippines, thus strengthening the arguments in favour of the present study by pointing out inadequacies in these materials for the needs of Filipino students. The limitations and clarifies the terms used in this study. The problem is the formulation of skill builders in English for training in four reading skills, namely : 1.) Finding the central or key thought. 2.) Making inferences. 3.)Reading to remember and to associate ideas. 4.) Outlining and organizing. Forty skill builders for Filipino students in high school are constructed on readability levels five and six, using the pooled judgment of critics and the Dale-Chall formula asbasis for classification. The use of the Dale-Chall formula is explained in the light of pressing needs in our reading programs. Chapter III describes the procedure in formulating the skill builders. Concepts and principles chosen to serve as guides for the study are listed. The selections are takenfrom local writings in English according to specific criteria based on these concepts and principles. In each selection the title, type of discourse, elements of style, themes and readability index are considered against the background of the modern concept of reading and the concepts and principles chosen. The next two chapters presents theskill builders thus formulated. Chapter IV presents the skill builders on level six. The order of arrangement is varied according to theme and interest value. An analysis and explanation of the general format is made and suggestions for the administration of the skill builders are offered. Chapter VI concludes the study with reiteration of its contribution to the improvement of reading programs in our schools. The two-fold nature of this contribution is explained further and its value in pointing the way towards utilizing local resources to solve the problem of inadequacy and insufficiency of supplementary reading materials in our schools is emphasized. Finally, the following recommendations are made as specific guides for exhausting the possibilities offered by our local resources for constructing reading skill builders adequate for Filipinos in high schools. 1.) In the University of the Philippines as well as in the public schools, research teams should be organized to work solely on reading skill builders using our local resources. 2. Research projects should choose whole selections as basis for exercises. 3.) The skill builders in this study should be administered on a large scale under experimental conditions for further revision and refinement. 4.) This study should be used to evolve norms for levels of difficulty in reading suitable to Filipinos. It can also be used as basis for constructing exercises developing skills other than those included here.